2022
DOI: 10.2147/idr.s374658
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, Serotype and Resistance of Salmonella Isolates from a Children’s Hospital in Hangzhou, Zhejiang, China, 2006–2021

Abstract: This research investigated the dynamics of antibiotic resistance in Salmonella and the epidemiology of Salmonella infection in children. These data can aid in the prevention and control of the Salmonella epidemic and the diagnosis and treatment of salmonellosis. Methods: In this study, we retrospectively reviewed and analysed data regarding epidemiology, clinical symptoms, Salmonella serotypes, and antibiotic resistance from the medical records of patients with Salmonella infections in Hangzhou Children's Hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
2
3

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 46 publications
1
2
3
Order By: Relevance
“…Interestingly, we found that the infection of Salmonella mostly occurred in autumn, which was consistent with other studies [26,31], indicating that autumn may be a season of high incidence for Salmonella infection. Further, the Salmonella isolates originated mainly from blood in our hospital, which may be the bloodstream infection caused by the strains transferred from gastrointestinal tract.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Interestingly, we found that the infection of Salmonella mostly occurred in autumn, which was consistent with other studies [26,31], indicating that autumn may be a season of high incidence for Salmonella infection. Further, the Salmonella isolates originated mainly from blood in our hospital, which may be the bloodstream infection caused by the strains transferred from gastrointestinal tract.…”
Section: Discussionsupporting
confidence: 93%
“…The high frequency of resistance to ampicillin and ampicillin/sulbactam in our study was similar to the previous reports from China [27,29], Italy [28], and Argentina [30], suggesting that ampicillin and ampicillin/sulbactam should be carefully prescribed for clinical treatment of infections caused by such strains. In addition, resistance to sulfamethoxazole/trimethoprim in our study was lower than those in previous domestic and foreign studies [29][30][31][32], however, relatively higher than those of other studies [33,34]. The reason may lie on the regional or strain difference.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…Typhimurium infections with children annually is not clear. This trend was also happened in other areas in China like Hangzhou, 39 Chongqing, 14 Ningbo 22 and so on. Data from the European Food Safety Authority (EFSA) showed that outbreaks caused by S .…”
Section: Discussionmentioning
confidence: 70%